The Effect Of Position Promotion And Religiusity On Employee Performance Through Motivation As An Intervening Variable At PT Pos Indonesia (Persero) Regional I Sumatra - Mutia Sari Dewi; Tri Inda Fadhila Rahma; Muhammad Ikhsan Harahap (International Journal of Management and Business Economics, 2023)
This study aims to determine the effect of promotion, religiosity, motivation on the performance of employees of PT Pos (Persero) Regional I Sumatra, both directly and indirectly. The method used in this study used quantitative methods by taking 30 respondents from PT Pos (Persero) Regional I Sumatra employees who were selected as research samples through non-probability sampling techniques, the sampling used in this study was saturated sampling. The questionnaire used hypothesis testing with SPSS software version 25 and the data analysis method used Path Analysis. The results of the study prove that promotion has an effect on employee performance at PT Pos Indonesia (Persero) Regional I Sumatra, religiosity has no effect on employee performance at PT Pos Indonesia (Persero) Regional I Sumatra, promotion has an effect on motivation at PT Pos Indonesia (Persero) Regional I Sumatra, Religiosity does not affect motivation at PT Pos Indonesia (Persero) Regional I Sumatra, Motivation influences employee performance at PT Pos Indonesia (Persero) Regional I Sumatra, Promotion through motivation as an intervening variable does not affect employee performance, Religiosity through motivation as an intervening variable does not affect employee performance, promotion and religiosity through motivation simultaneously influence employee performance at PT Pos Indonesia (Persero) Regional I Sumatra.